ON THE ANISOTROPIC BOUNDARY VALUE PROBLEM, CONNECTED WITH HELMHOLTZE-SCHRÖDINGER ЕQUATION, UNDER THE BOUNDARY CONDITIONS OF THE FIRST AND SECOND TYPE - Hosseiny Matikolai, S.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2011)
In this paper we consider the solvability of the boundary value problem, connected with the anisotropic Helmholtz-Schrödinger equation, under the boundary conditions of the first and second type on the line y=0.